The synthesis and characterisation of controlled thin sub-monolayer films of 2-anthraquinonyl groups on graphite surfaces - Li, Q; Batchelor-McAuley, C; Lawrence, N; Hartshorne, R; Compton, R (2011)
Aryl (Ar) modified carbon electrodes are of importance for a range of sensing and electrocatalysis applications. However the majority of the modification methods result in a thick polymer layer. The commonly applied method using electrochemical reduction of diazonium salt (to form Ar) leads to polymerisation at very low surface coverages. We report an alternative approach using a methodology based on the pre-adsorption of the anthraquinone-2-diazonium salt (2-AQN+2BF-4) onto an edge plane pyrolytic graphite electrode to form a thin unreacted sub-monolayer film. After transfer to a buffer solution containing no diazonium salt, the adsorbed material then thermally decomposes at room temperature and completes the modification procedure. When the surface coverage of anthraquinonyl groups is below ca. 2 × 10-10 mol cm-2, non-broadened voltammetric peak signals were observed for the electro-reduction of the surface bound 2-AQ groups in sodium hydroxide buffer solution. This near-ideal voltammetric response reflects the mode of attachment which is likely via ester linkages formed between reaction of carbocation intermediates (Ar+) and carboxylate groups present on the edge plane sites regions of the graphite electrode. The desired thin sub-monolayer has significant importance in creating tailor made interfaces. It not only provides molecular level control over the surface layer, but also provides physical insight into the origins of the observed non-ideal behaviour of the redox modified surfaces. © 2011 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.